Production of extracellular alkaline protease by immobilization of the marine bacterium Teredinobacter turnirae - Elibol, M; Moreira, AR (Elsevier Sci Ltd, 2003)
Cells from a marine bacterium, Teredinobacter turnirae cells were immobilized in calcium alginate beads and used for alkaline protease production. The maximum protease activity was obtained at 3% (w/v) sodium alginate and 3% CaCl2 concentrations with a 1/2 cell/alginate ratio, i.e. 2400 U/ml. There was no significant difference in the maximum protease activity between three bead sizes used. A drastic fall in protease production was observed when the beads were treated with glutaraldehyde. The beads were used for eight successive fermentation batches each lasting 72 h. It was also observed that there was a similar to3.5-fold increase in volumetric productivity of protease after the fourth cycle. (C) 2003 Elsevier Science Ltd. All rights reserved.
Keywords: shipworm; Teredinobacter turnirae; alkaline protease; immobilization; calcium alginate